The Influence Of Financial Literacy, Lifestyle And Fear Of Missing Out On The Financial Behavior Of Generation Z In Pontianak City - Ardilla, Ridha; Suryadi, Edy (JHSS (JOURNAL OF HUMANITIES AND SOCIAL STUDIES), 2019)
This research aims to find out how financial literacy, lifestyle and fear of missing out influence the financial behavior of Generation Z in Pontianak City. The type of research used is associative research. From this research it was concluded that: 1) Most of the Generation Z respondents in Pontianak City were female, 21 years old, and had a high school education. 2) The multiple linear regression equation of the influence of financial literacy, lifestyle, fear of missing out on the financial behavior of Generation Z in Pontianak City is:Y = 1.088 + 0.572X1 + 0.157X2 + 0.027X3 + e. 3) The correlation coefficient (R) is 0.637, meaning that the variables financial literacy, lifestyle and fear of missing out on the financial behavior of generation Z have a strong relationship. 4) The coefficient of determination obtained is 0.405, meaning that financial literacy, lifestyle and fear of missing out have a 40.5% influence on generation Z's financial behavior, while the remaining 59.5% is influenced by other variables not included in the research This. 5) The results of the simultaneous influence test (F test) show that F count is 33.192 F Table 2.66, so that Ho is rejected. Ha is accepted, meaning that financial literacy, lifestyle and fear of missing out simultaneously influence the financial behavior of Generation Z in Pontianak City. 6) The results of the t test (partial influence test) show that financial literacy partially has a significant effect on financial behavior. Lifestyle partially has a significant effect on financial behavior. And fear of missing out partially does not have a significant effect on financial behavior.